COLLABORATIVE STRATEGIES: IMPROVING COOPERATION AND COMMUNICATION SKILLS IN THE CLASSROOM - Bali, Muhammad Mushfi El Iq; Rosida, Aisyatur; Gunawan, Zaini (STKIP Pesisir Selatan, 2025)
This research aims to improve the cooperation and communication skills of class V MI Nurus Salam students through collaborative strategies. This research used the classroom action research (CAR) method which was carried out in two cycles, each consisting of three meetings. Each cycle includes planning, implementation, observation and reflection stages. Data was collected through observation, questionnaires and interviews to assess the development of students' communication and collaboration skills. The results of this research indicate that collaborative strategies are effective in improving students' communication and collaboration skills. This research contributes to the development of learning methods at Madrasah Ibtidaiyah, especially in increasing students' active involvement in learning. Before the intervention, the level of student completion in communication and collaboration skills was still low, with only 38.46% of students completing it. After implementing collaborative strategies in cycle I, communication skills increased to 76.93% and collaboration skills reached 61.54%. However, some students are still less active in group discussions and interactions. Therefore, the strategy was improved in cycle II with clearer instructions and encouragement for active participation. In cycle II, communication skills increased to 92.30%, while collaboration skills reached 84.61%. Student completion levels also increased from 38.46% in the pre-cycle stage to 84.61% after cycle II.